Ammonia and Nitrous Oxide Losses Following Applications of Ammonium Sulfate to Flooded Rice - Freney, JR; Denmead, OT; Watanabe, I.; Craswell, E.T. (Commonwealth Scientific and Industrial Research Organisation, 1981)
Ammonia volatilization from applications of ammonium sulfate to a wet season crop of flooded rice in the Philippines was measured directly by a micrometeorological technique. Prior to transplanting the rice, ammonium sulfate (80 kg nitrogen ha-1) was broadcast over the flooded soil and incorporated by harrowing. A further 40 kg nitrogen ha-1 was broadcast at the panicle initiation stage. The soil pH was 6.7, while the pH of the floodwater varied from 7 . 5 to 9.5 during the course of the experiment. Loss of ammonia was detected immediately after application of ammonium sulfate and continued for approximately 7 days. Ammonia volatilization rates were highest in the middle of the day and declined each evening following the diurnal variations in water temperature and wind speed. More ammonia was lost from the fertilizer applied at the panicle initiation stage (10.6%) than from the pre-planting application (5.1 %). The overall measured loss of ammonia was small and amounted to approximately 7 % of the total nitrogen applied to the crop. Nitrous oxide losses, measured with a chamber system, amounted to only 0.1 % of the nitrogen applied as ammonium sulfate.